2017
DOI: 10.1111/fare.12294
|View full text |Cite
|
Sign up to set email alerts
|

Legal Counseling and the Marriage Decision: The Impact of Same‐Sex Marriage on Family Law Practice

Abstract: Objective To examine the role of family law attorneys in providing counsel regarding the legal rights, vulnerabilities, and implications of marriage for their lesbian, gay, bisexual, and transgender (LGBT) clients. Background Although the acquisition of state and federal marital rights could result in a convergence of practice experiences for family lawyers representing LGBT and heterosexual clients, the contentious legal history surrounding LGBT individuals could continue to produce different client demands s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…LGTBI (Acosta, 2017;Baumle, 2018). En el estudio realizado vemos que, de momento, son escasos los estudios en las revistas científicas revisadas que se centren en las problemáticas específicas de la protección de estos colectivos o asociaciones o situaciones asimiladas a la familia.…”
Section: Algunas Consideraciones Sobre El Enfoque De Las Investigacio...unclassified
“…LGTBI (Acosta, 2017;Baumle, 2018). En el estudio realizado vemos que, de momento, son escasos los estudios en las revistas científicas revisadas que se centren en las problemáticas específicas de la protección de estos colectivos o asociaciones o situaciones asimiladas a la familia.…”
Section: Algunas Consideraciones Sobre El Enfoque De Las Investigacio...unclassified
“…While cultural understandings and everyday practices of marriage and family influence the configuration of the national welfare regime, this configuration also structures people's decisions on how to activate and utilize their family membership, such as the decision to marry (Bernstein et al, 2016; Lin & Rantalaiho, 2003; Papadopoulos & Roumpakis, 2017). Studies on SSP in the West have shown that the legal and material benefits of marriage and the strength of the national social safety net significantly influence people's decision to form a legal SSP (Baumle, 2018; Baumle & Compton, 2015; Beekman, 2012; Bernstein et al, 2016; Dickens et al, 2009; Waaldijk, 2020). Marriage is more desirable for same‐sex couples in countries where social safety nets are weak, because it provides access to a certain number of benefits, both material and nonmaterial, reserved for married partners (Bernstein et al, 2016).…”
Section: Family Policies Family Experiences and The Statementioning
confidence: 99%